Balanced Scorecard sebagai Alternatif Alat Penilaian Kinerja untuk Pengukuran Kinerja pada BPR âMJPâ - Kriswanto, Kriswanto (Binus Business Review, 2015)
The purpose of this study is to provide an alternative implementation of the Balanced Scorecard to improve the performance of the company in the long run. The alternative is recommended, because the measurement of the performance of the company was considered inappropriate. This is because at this time, the company uses traditional performance measurement which only emphasizes the financial aspects only. Study of literature and field observations have been made to obtain information related to the problem that occurred in the company. A questionnaire was used as a tool to look at from the side of the customers and workers during the traditional performance measurement is not a measurement element. Performance of the company in 2011 was less than satisfactory, due to a decrease in operating income, which also resulted in the companys net profit declined. Satisfactory results were obtained through questionnaires to customers who indicate that customers have been satisfied with the performance of the company. Questionnaire distributed to workers also showed satisfactory results that affect the companys internal business processes. It is known when the measurement of internal business process perspective, and learning and growth perspective is done. Suggestions and improvements to the company will be adapted to the circumstances of the company.